Efficacy of soil-borne entomopathogenic fungi against subterranean termite, Coptotermes curvignathus Holmgren (Isoptera: Rhinotermitidae) - Muhammad Amali Kamarudin; Sumaiyah Abdullah; Wei Hong Lau (Egyptian Journal of Biological Pest Control, 2022)
Abstract Background Coptotermes curvignathus Holmgren (Isoptera: Rhinotermitidae) is a subterranean termite that poses serious damage to oil palm and rubber trees. Chemical pesticides could cause negative effect to human and the environment in long-term usage. The use of entomopathogenic fungi (EPF) to suppress the population of subterranean termites is in favour when compared to chemical pesticides because they do not harm to the environment and non-target organisms. The study aimed to isolate and identify the EPF from the soil using yellow mealworm larvae of Tenebrio molitor Linnaeus in the baiting method and assessed their efficacy against subterranean termite, C. curvignathus. Result Eleven EPF isolates were successfully isolated from the oil palm plantation in Universiti Putra Malaysia, namely: Aspergillus auricomus (UPM-A1C-1), A. caelatus (UPM-A1C-2), Metarhizium anisopliae var anisopliae (UPM-A2C-1, UPM-A3C-1, UPM-A3C-2, UPM-A5C-1 and UPM-A10C-1), Purpureocillium lilacinum (UPM-A2C-3 and UPM-A7C-1), Cordyceps javanica (UPM-A2C-5), and M. pinghaense (UPM-A13C-2). The identity of these EPF were confirmed by morphological and molecular characteristics. All EPF yielded 100% mortality in C. curvignathus in 10 days after inoculation (DAI), except UPM-A1C-1 and UPM-A1C-2 after exposure to 1 × 107 conidia ml−1. UPM-A2C-5 Cordyceps javanica yielded the highest mycelia formation (69%) after 6 DAI. The LT50 values varied from 3.90 to 7.75 days. UPM A2C-1 M. anisopliae var anisopliae showed the lowest LT50 (3.90 days), while UPM-A1C-1 Aspergillus auricomus showed the highest LT50 (7.75 days). The lowest LC50 value (1.49 × 105 conidia ml−1) was recorded in UPM A2C-1  M. anisopliae var anisopliae. Conclusions The present study confirmed the soilborne EPF with potential insecticidal activity against C. curvignathus. UPM-A2C-1 M. anisopliae var anisopliae was a potential biological control agent against Subterranean termite, C. curvignathus due to its virulence score and high percentage of mycelia formation after 6 DAI. The data reported in the present study, particularly using P. lilacinum, M. pinghaense, Aspergillus auricomus, A. caelatus and C. javanica with potential insecticidal activity against C. curvignathus, are new records.